Cover Image: Volume 82 Issue 6. Issue 6 (23rd March 2022) - Ozbek, Busra; Ertunc, Onur; Erickson, Andrew; Vidal, Igor D.; Gomes‐Alexandre, Carolina; Guner, Gunes; Hicks, Jessica L.; Jones, Tracy; Taube, Janis M.; Sfanos, Karen S.; Yegnasubramanian, Srinivasan; De Marzo, Angelo M.
Abstract : Cover Caption: The cover image is based on the Original Article Multiplex immunohistochemical phenotyping of T cells in primary prostate cancer by Busra Ozbek et al., https://doi.org/10.1002/pros.24315 .